An 8 Gb/s/pin 9.6 ns Row-Cycle 288 Mb Deca-Data Rate SDRAM With an I - Kim, K.-h (IEEE Journal of solid state circuits)
This paper proposes a deca-data rate clocking scheme and relevant I/O circuit techniques for a multi-Gb/s/pin memory interface. A deca-data rate scheme transmits 10 bits in one external clock cycle to transfer an error control code along with original data seamlessly without a timing bubble. A 288 Mb SDRAM has been designed using the proposed scheme combined with fast cycling core techniques to have both high I/O bandwidth and fast random cycling. Measured results show that the chip exhibits per-pin data rate of 8 Gb/s and row cycle time of 9.6 ns